1993
DOI: 10.1063/1.354020
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric and photoacoustic investigation of KNO3 phase transitions

Abstract: Results of a thermodynamic study of the phase transitions of powdered KNO3 at two impurity concentrations (99.999% pure and 99.9% pure) are reported. Transition onset and peak temperatures have been measured between 350 and 420 K using both heat flow and photoacoustic calorimetry. The transition temperatures and characteristics observed with both techniques show excellent agreement. Specific-heat values calculated from scanning and stepped temperature heat-flow data, utilizing both positive and negative temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
1
9
0
2
Order By: Relevance
“…It has been reported that the preparation of the composite films of nano 2 , selenide with PVa using solvent cast technique was helpful in controlling the growth of nano 2 , and selenide nanoparticles [10], [22]. Many studies using techniques such as far infrared [25], neutron diffraction [26], inelastic neutron scattering [27], raman spectroscopy [28], [29], X-ray [30]- [32], differential scanning calorimetric [33]- [35], dielectric [36], electrical and thermal conductivity [36], [37], and ferroelectric [38]- [41], have been carried out in the past by various researchers to examine the nature of the phase transitions in Kno 3 . The technological interest in Kno 3 thin films originates due to the reason that these films have low operating voltage and fast switching response.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the preparation of the composite films of nano 2 , selenide with PVa using solvent cast technique was helpful in controlling the growth of nano 2 , and selenide nanoparticles [10], [22]. Many studies using techniques such as far infrared [25], neutron diffraction [26], inelastic neutron scattering [27], raman spectroscopy [28], [29], X-ray [30]- [32], differential scanning calorimetric [33]- [35], dielectric [36], electrical and thermal conductivity [36], [37], and ferroelectric [38]- [41], have been carried out in the past by various researchers to examine the nature of the phase transitions in Kno 3 . The technological interest in Kno 3 thin films originates due to the reason that these films have low operating voltage and fast switching response.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the DSC scan of the composite film, no peak appears below 114.4 • C up to room temperature, which indicates that phase III exists up to room temperature. The ferroelectric composite film can possess ferroelectric phase III at room temperature whereas KNO 3 does not possess phase III at room temperature [11]. Therefore, the composite can have the advantage to be ferroelectric at room temperature in thin film form.…”
Section: Dsc Measurementsmentioning
confidence: 99%
“…Many studies such as far infrared, 4,7 neutron diffraction, 8 inelastic neutron scattering, 9 Raman spectroscopy, 1,10,11 X‐ray, 11–13 differential scanning calorimetric, 14–16 dielectric, 5,17 electrical 17 and thermal conductivity, 18 and ferroelectric, 19–22 have been carried out in past by many researchers to examine the nature of the phase transitions in KNO 3 .…”
Section: Introductionmentioning
confidence: 99%